2019
DOI: 10.5539/jas.v11n16p107
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Efficiency and Nutrient Acumulation of Maize Cultivated in Soils With High Al-KCl Content

Abstract: Most Brazilian soils are weathered and acidic, generally with exchangeable aluminum levels toxic to plants. Aluminum content can exceed 10 cmolc kg-1 in certain soils, but does not interfere in plant nutrient absorption, transport and accumulation. This study aimed to assess whether the high aluminum levels extracted with 1 mol L-1 KCl solution affect the nutritional efficiency of maize plants grown in acidic soils in areas of Brazilian states (AC: profile 9, PE, SC and RS) never before cultivated. To that end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The low Mg contents of the seeds in both soils compared to the other nutrients (except Ca) (Table 4) may be related to its competition with K and Ca for the absorption sites in the plant roots (Senbayram, Gransee, Wahle, & Thiel, 2015;Bruns, 2016;Cunha et al, 2019). Senbayram et al (2015) reported that K absorption by plants is usually not impaired in soils whose Mg contents are higher than the K contents, as observed in this Acta Scientiarum.…”
Section: Chemical Composition Nutrient Accumulation In Seeds and Soyb...supporting
confidence: 55%
See 3 more Smart Citations
“…The low Mg contents of the seeds in both soils compared to the other nutrients (except Ca) (Table 4) may be related to its competition with K and Ca for the absorption sites in the plant roots (Senbayram, Gransee, Wahle, & Thiel, 2015;Bruns, 2016;Cunha et al, 2019). Senbayram et al (2015) reported that K absorption by plants is usually not impaired in soils whose Mg contents are higher than the K contents, as observed in this Acta Scientiarum.…”
Section: Chemical Composition Nutrient Accumulation In Seeds and Soyb...supporting
confidence: 55%
“…The similarity between the control, pure siltstone, and tephrite treatments may be related to the nutrient dilution (Colombari, Lanna, Guimarães, Martins, & Cardoso, 2018;Cunha et al, 2019) in the plants cultivated in soils managed with limestone, olivine melilitite, and siltstone + olivine melilitite associated or not with manure at their respective doses, which presented the highest TDM productions (Table 5) compared to the other treatments of pods and seeds (data not shown). In addition, the low TDM production may have led to a higher nutrient concentration, but statistically similar to the control (Table 5), in the different parts of the plant cultivated in the soils subjected to the treatments with the rock dusts siltstone and tephrite.…”
Section: Chemical Composition Nutrient Accumulation In Seeds and Soyb...mentioning
confidence: 90%
See 2 more Smart Citations
“…From TDM and the N, P, K, Ca, and Mg contents, the accumulated amounts of these nutrients in the plant tissue were calculated according to the equation: N Amacro (mg) = TDM (mg) x nutrient concentration (%) / 100 (Cunha et al, 2019), where N Amacro corresponds to the amount of macronutrient accumulated in the vegetal tissue (aerial part + roots) of the tested plants.…”
Section: Methodsmentioning
confidence: 99%